A Method for Generating Riddle-Driven Plots for Games - Piotr CYBULSKI (Communications of International Proceedings, 2025)
Designing activities when the attention span of participants is short is not an easy task. One solution is to provide unique experience to participants. This article presents a method for generating a riddle-driven plot for games and other gamified activities. The proposed method allows to trace progress of a plot and checking if a generated plot is cognizable by a player. It is also possible to incorporate story volumes into a generation process. Formal definitions of structures used by the method are presented as well as an example of expressiveness of its components. The designed method makes checking cognizability of a plot feasible in polynomial time to the number of plot elements and relations between them.